Contribution of Dug-Out Wells to Salmonella Dissemination in Kwaebibirem District of Ghana - P.K. Feglo; M. P. Dakorah (European Scientific Journal, ESJ, 2017)
Typhoid fever is rare in the developed world, but in Kwaebibirem District of Ghana, Salmonella infections are very common. Typhoid and paratyphoid fevers in addition to gastroenteritis are frequently reported. The reservoir, prevailing Salmonella species and their antimicrobial susceptibility patterns are not known, but in Ghana treatment of these infections are mostly empirical. 464 samples (270 stool and 194 blood) were collected from patients and 188 water samples were collected from different water sources in Kwaebibirem District and cultured for Salmonella at St. Dominic Hospital, Akwatia. Salmonella prevalence of 11.6% (54/464) among patients and 2.7% (5/188) from dug-out wells were obtained. Total viable bacterial count in the water samples averaged 2.56 x103 -1.2 x 1013per milliliter. Five (5) out of 51 (9.8%) dug-out wells yielded Salmonellae upon culture. Typhoidal Salmonellae [11% (6/54)] and 68.6% (38/54) non-typhoidal Salmonellae were isolated from patients. The most affected age group ranged 6-15years with prevalence of 42.6% (23/54). The most frequent isolated was Salmonella Typhi 20% (11/54) followed by Salmonella Enterica, 29.6% (16/54). The Salmonella isolates were all susceptible to the cephalosporins (cefoxitin, cefotaxime, cefepime) the carbapenems (imipenem and meropenem) the quinolones (norfloxacin and ciprofloxacin) and the aminoglycoside (amikacin). Their resistant proportions to other drugs were ampicillin (69.5%), piperacillin (69.5%) and co-trimoxazole (76.3%). Salmonella infections were common in Kwaebibirem District, and home owned dug-out wells posed risk of Salmonella transmission to the people.